2011
DOI: 10.4103/0971-5851.89778
|View full text |Cite
|
Sign up to set email alerts
|

Bone tumors in a tertiary care hospital of south India: A review 117 cases

Abstract: Background:Bone tumors remain a daunting challenge to orthopedic surgeons. The challenge is heightened in developing countries due to limited diagnostic and therapeutic facilities as well as due to ignorance. The published literature on this subject is sparse in our environment.Objective:To determine the pattern of bone tumors including their relative frequencies, age and sex distributions, anatomical sites of occurrence and clinico-pathological characteristics as seen in a tertiary care hospital of south Indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
14
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 5 publications
19
14
1
Order By: Relevance
“…They were seen predominantly in the 5 th (30%) and 6 th (27.5%) decade similar to Jain study with male predominance. [15] Of the 40 cases of metastatic bone tumours 37.5% showed metastasis from lung carcinoma followed by 22.5% from GIT, finding of our study similar to Jain study who also reported lung carcinoma (38.46%) metastasis to bone followed by GIT (23.07%). [15] Vertebra was the most common site involved 32 cases (80%) [16] Radiologically destruction of the vertebra was the most common finding (Figure 4d).…”
Section: Vascular Tumoursupporting
confidence: 88%
See 1 more Smart Citation
“…They were seen predominantly in the 5 th (30%) and 6 th (27.5%) decade similar to Jain study with male predominance. [15] Of the 40 cases of metastatic bone tumours 37.5% showed metastasis from lung carcinoma followed by 22.5% from GIT, finding of our study similar to Jain study who also reported lung carcinoma (38.46%) metastasis to bone followed by GIT (23.07%). [15] Vertebra was the most common site involved 32 cases (80%) [16] Radiologically destruction of the vertebra was the most common finding (Figure 4d).…”
Section: Vascular Tumoursupporting
confidence: 88%
“…[15] Of the 40 cases of metastatic bone tumours 37.5% showed metastasis from lung carcinoma followed by 22.5% from GIT, finding of our study similar to Jain study who also reported lung carcinoma (38.46%) metastasis to bone followed by GIT (23.07%). [15] Vertebra was the most common site involved 32 cases (80%) [16] Radiologically destruction of the vertebra was the most common finding (Figure 4d). Radiologically, destructive focus with moth eaten appearance, cortical disruption, extension into soft tissue and periosteal new bone formation may be present.…”
Section: Vascular Tumoursupporting
confidence: 88%
“…Similar results were obtained in few Indian studies. 12,13 Osteosarcoma constitutes the most common primary bone tumor in young and adolescents. It occurs most frequently 11-20 years, occurring in the metaphysis, mostly in lower end of femur followed by upper end of tibia.…”
Section: Discussionmentioning
confidence: 99%
“…12,13,18 Giant Cell Tumor commonly involves the long bones affecting lower end of femur, upper end of tibia and lower end of radius. It also involves the fibula, humerus, skull and less commonly the sacrum.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, very few studies have been conducted in this field. Among different types of primary bone cancer, osteosarcoma constitutes the highest proportion (36%) of cases, followed by chondrosarcoma, osteoclastoma and Ewing's sarcoma 6 .…”
Section: Introductionmentioning
confidence: 99%